Uma proposta para o ensino de função polinomial do 1º grau utilizando a plataforma do app Inventor 2 e o software Desmos - COSTA, Bruno Sebastião Rodrigues da (Universidade Federal do Pará, 2021)
The general objective of this research is to present a proposal for teaching 1st Degree Polynomial Function for High School, through the platform "App Inventor 2" and software "Desmos". To this end, a literature review was conducted from 2015 to 2020 in websites such as the theses and dissertations database of the Coordination for the Improvement of Higher Education Personnel (CAPES), Google Scholar, Scientific Electronic Library Online (SciELO), and in official documents such as the Educational Guidelines Complementary to the National Curriculum Parameters (PCN+ ENSINO MÉDIO), the National Curriculum Guidelines for Secondary Education (PCNEM), the National Common Curricular Base (BNCC) and the Curriculum Document of the State of Pará, in its preliminary version of the High School stage, and the experiences we have lived, which contributed significantly to the development of our Educational Product. With this, we will propose a digital booklet with activities, using the Digital Information and Communication Technologies (TDICs), to teach 1st Degree Polynomial Function using "App Inventor 2" and "Desmos" software. This proposal was motivated by the difficulties encountered in my experiences as a teacher, which were identified by teachers/students when teaching/learning 1st Degree Polynomial Function. For this, we used as methodology, qualitative research, described according to Mazzotti (1991), Minayo (1994) and Siva (2012), and as method the integrative review as a proposed literature review, based on the authors Bento (2011) and Botelho, Cunha and Macedo (2011). Therefore, our research is justified because we understand that this teaching proposal, to teach the mathematical object 1st Degree Polynomial Function through the aforementioned tools, can provide a motivating, facilitating and dynamic teaching, favoring student learning. Thus, these tools can help positively in the construction of mathematical knowledge, contributing to the process of teaching and learning the content of 1st Degree Polynomial Function.